Influence of Vitamin-E and Selenium Supplementation on the Growth Performance and Antibody Responses of Layer Chicks - G. KANCHANA,; G.P. JEYANTHI, (International Journal of Pharma and Bio Sciences, 2010)
An experiment was conducted to study the effect of vitamin E and selenium yeast supplementation on the growth performance and some immune parameters with two hundred and ten commercial straight run day-older layer chicks. The chicks were randomly allotted into seven treatment groups with three replicates of ten chicks each. The chicks were fed basal diet (T1), basal diet with 100 mg/kg vitamin E (T2), basal diet with 200 mg/kg vitamin E (T3), basal diet with 0.2 mg/kg selenium (T4), basal diet with 0.4 mg/kg selenium (T5), basal diet with 100 mg/kg vitamin E plus 0.2 mg/kg selenium (T6), and basal diet with 200 mg/kg vitamin E plus 0.4 mg/kg selenium (T7) for eight weeks period. No significant difference was found in the body weight of layer chicks for the first four weeks among the treatment groups but the body weight of groups (T6 and T7) receiving both vitamin E and selenium was significantly increased (P<0.05) at the end of 8 weeks period. The feed intake of layer chicks did not vary significantly between treatment groups. Chicks receiving supplements of 100 mg vitamin E/kg and 0·2 mg selenium/kg produced significantly higher HA titre against SRBC (P<0.01), HI titre against NDV (P<0.01) and QAGPT titre against IBDV (P<0.01). The results suggested that vitamin E and selenium might provide higher level of protection against natural immune challenges.